DNA extraction from silica gel-preserved common bean (Phaseolus vulgaris L.) leaves - Ssekamate, Allan Male; Kato, Fred; Mukankusi, Clare (Academic Journals, 2018)
Extraction of non-degraded and contaminant-free DNA from field specimen requires collection under liquid nitrogen which is not readily available in resource constrained laboratories in low and middle income countries (LMICs). A method of extracting DNA from silica gel-preserved common bean (Proteus vulgaris L.) leaves is presented. The method, which does not involve the use of phenol, chloroform or isoamyl alcohol also obviates the need for low temperature incubation during the DNA extraction steps and the grinding of desiccated leaf tissue in liquid nitrogen. It relies on inactivating proteins using SDS and proteinase K along with precipitation of polysaccharides using a high salt solution (0.8 M NaCl). DNA is further purified by exploiting its insolubility in aqueous media. High quality pure DNA (mean concentration 2.84 ± 0.013 µg/g of dry leaf tissue) with mean DNA purity values of 2.1 ± 0.1 was extracted. The DNA was also found to be free of protein and polysaccharide contamination. This method enables DNA amplification using molecular markers routinely used in molecular biology laboratories like random amplified polymorphic (RAPD) markers, inter simple sequence repeat (ISSR) markers, sequence-characterized amplified region (SCAR) markers and simple sequence repeat (SSR) markers. The findings of this study show that it is possible to obtain high quality DNA from leaf tissue preserved in silica gel. The method used in this research will be invaluable to resource constrained laboratories in low and middle income countries (LMICs) that cannot afford to buy or access liquid nitrogen in order to extract high quality DNA and for research groups undertaking field surveys that require several days or weeks off station without laboratory freezers to maintain the integrity of the tissues which is crucial for obtaining high quality DNA.